Leveraging Dashboard Analytics for Enhanced Sustainability Monitoring in University Campuses - Masnita Misiran; Zahayu Md Yusof; Nor Idayu Mahat; Suhaida Abdullah; Hasimah Sapiri (Human Sustainability Procedia, 2025)
The use of dashboard analytics—more especially, Google Onlooker Studio—as an affordable and easily available instrument for tracking sustainability initiatives on college campuses is examined in this article. This paper proposes a framework for using dashboard analytics to support data-driven decision-making processes in promoting sustainability within academic institutions, drawing on real-world examples such as the creation of dashboards for UUM Living Campus 2030, the Drive-thru Recycle Center initiative, and University Social Responsibility community outreach. These dashboards make it possible to track, evaluate, and optimize many facets of sustainability projects, which will ultimately result in better results and more effective use of available resources.